Strategic Alliances In Shanghai Jahwa Co., Ltd Of China - Xu, Yang (2005)
Case study of Shanghai Jahwa is conducted with the objectives of studying the performance of SJ, and make suggestions to its development. This study focuses on exploring, evaluating and discussing Shanghai Jahwa's recent and future conditions in the marketplace based on the research conducted and its written case.